1982
DOI: 10.2527/jas1982.5551033x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Testes Size and Sperm Number in Hereford Bulls

Abstract: Paternal half-sib heritability and genetic correlation estimates were obtained utilizing data from 578 Hereford bulls from 66 sires. Bulls were maintained in three lines (weaning weight, postweaning gain and control) of an ongoing selection project. Growth performance traits studied were adjusted 205-d weaning weight, 365-d weight, individual feed efficiency, sonoray fat thickness and postweaning gain. Heritability estimates for these traits were .15 +/- .17, .33 +/- .19, .46 +/- .21, .28 +/- .18 and .52 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 0 publications
3
15
0
1
Order By: Relevance
“…This correlaCorrelation coefficient (r) 0.21 0.10 -0.14 Table 3. Correlation coefficients Propertics between thc testosterone values of blood (n = 40) __ at the beginning and at Testosterone content of blood plasma before the GnRB treatment (nmolil) the end Of the self-performance Testosterone content of blood plasma after the GnRH treatmcnt (nmolil) Changc of testosterone content of the blood plasma (nmolil) tion is not as close as some previous (r = 0.92) results (Aehnelt et al 1972), however, it is nearly the same as some other (r = 0.49) findings (Neely and Johnson 1988). From the authors previous experiment with Charolais breeding bulls, correlation values of r = 0.6-0.7 were found in two different stock farms (J. T6zsCr et al unpubl.…”
Section: Resultssupporting
confidence: 80%
“…This correlaCorrelation coefficient (r) 0.21 0.10 -0.14 Table 3. Correlation coefficients Propertics between thc testosterone values of blood (n = 40) __ at the beginning and at Testosterone content of blood plasma before the GnRB treatment (nmolil) the end Of the self-performance Testosterone content of blood plasma after the GnRH treatmcnt (nmolil) Changc of testosterone content of the blood plasma (nmolil) tion is not as close as some previous (r = 0.92) results (Aehnelt et al 1972), however, it is nearly the same as some other (r = 0.49) findings (Neely and Johnson 1988). From the authors previous experiment with Charolais breeding bulls, correlation values of r = 0.6-0.7 were found in two different stock farms (J. T6zsCr et al unpubl.…”
Section: Resultssupporting
confidence: 80%
“…These values are somewhat less than the lower plateaus of number of sperm in the semen ( Figure 5). High correlations of testicular size with sperm output have been found in swine (Wilson et al, 1977;Egbunike and Elemo, 1978;Neely et al, 1980;Fent et al, 1983), sheep (Knight 1977(Knight , 1984, and cattle (Hahn et al, 1969;Almquist et al, 1976;Coulter et al, 1976;Neely et al, 1982). None of the studies compared lines that differed in testis size due to selection.…”
Section: Discussionmentioning
confidence: 97%
“…Scrotal circumference is easy and inexpensive to measure, has moderate heritability, and is reported to be favorably associated with female fertility (Brinks et al, 1978;Morris et al, 1992;Vargas et al, 1998). Positive genetic correlations between SC and growth traits (Bourdon and Brinks, 1986;Smith et al, 1989;Keeton et al, 1996) and between SC and semen quality traits (Neely et al, 1982;Knights et al, 1984;Smith et al, 1989) have been reported.…”
Section: Introductionmentioning
confidence: 99%